What does the CDS market imply for a U.S. default? - Luca Benzoni; Christian Cabanilla; Alessandro Cocco; Cullen Kavoussi (Federal Reserve Bank of Chicago, 2023)
As the debt ceiling episode unfolds, we highlight a sharp increase in activity across the U.S. credit default swaps (CDS) market and infer the likelihood of a U.S. default from these market prices. Beginning in January 2023, we document a significant increase in U.S. CDS trading activity and positions, accompanied by a spike in CDS premiums. We estimate an increase in the market-implied default probability from about 0.2-0.3% in 2022, to approximately 1% in 2023. Yet, this default probability currently remains lower than what we find for the periods leading up to the 2011 and 2013 debt ceiling episodes, due in part to the cheapening of deliverable Treasury collateral to CDS contracts.
Keywords: G10; G12; G18; G28; E32; E43; E44; 330; U.S. default; U.S. CDS; default probabilities; sovereign CDS; debt ceiling